ChemInform Abstract: Asymmetric Mannich Synthesis of α‐Amino Esters by Anion‐Binding Catalysis. Issue 12 (March 2015) - Wasa, Masayuki; Liu, Richard Y.; Roche, Stephane P.; Jacobsen, Eric N.
Abstract The chiral aminothiourea catalyst operates cooperatively by generating an iminium ion through chloride abstraction and an enolate by deprotonation, followed by stereoselective C‐C bond formation between both reactive intermediates associated non‐covalently within the catalyst framework.